Vatica rassak wood waste-derived activated carbon for effective Pb(II) adsorption : Kinetic, isotherm and reusability studies - Teong, Chi Qi; Setiabudi, H. D.; El-Arish, Nurul Amirah Salihah; Bahari, Mahadi; Teh, L. P. (Elsevier Ltd, 2019)
Vatica Rassak wood waste-derived activated carbon (ACVRW) was employed for lead (Pb(II)) adsorption. Batch adsorption tests were executed to investigate the influences of contact time (t = 0-60 min), ACVRWdosage (m = 0-5 g L-1), initial pH (pH = 2-10), and initial Pb(II) concentration (Co= 10-200 mg L-1) towards Pb(II) elimination. The best adsorption conditions were found at t = 55 min, pH = 6, and m = 2 g L-1, with optimal Pb(II) uptake of 149.25 mg g-1. The equilibrium data demonstrated high linearity with the pseudo-second-order kinetic model as well as the Langmuir isotherm model. The characterization results showed the vital role of ACVRW's physicochemical properties in the Pb(II) adsorption process. It is observed that the surface of the adsorbent after adsorption became ruptured and many fine particles attached on it. Moreover, the pore size of the adsorbent also decreased after adsorption. The practicability of ACVRWwas verified by its excellent performance in the reusability study with slight reduction in Pb(II) removal of 10.72% after five cycles. This study proved that ACVRWpossessed significant features to be employed as a low-cost activated carbon for the elimination of Pb(II).